Autoresuscitation and clinical authority in death determination using circulatory criteria. (May 2022) - van Beinum, Amanda; Hornby, Laura; Scales, Nathan; Shemie, Sam D.; Dhanani, Sonny
Highlights: - The clinical process of determining death using circulatory criteria is unsettled. - Cardiac activity after determination of death is perceived as "autoresuscitation". - Intensive care life support technologies help establish dying as normal or abnormal. - Dying trajectories are interpreted to maintain confidence in the definition of death.